Introducing language typology - Moravcsik, Edith A. (Cambridge : Cambridge University Press, 2013)
'Language typology identifies similarities and differences between languages of the world. This textbook provides an introduction to the subject which assumes minimal prior knowledge of linguistics. It offers the broadest coverage of any introductory book, with sections on historical change, language acquisition and language processing. Students will become familiar with the subject by working through numerous examples of cross-linguistic generalizations and diversity in syntax, morphology and phonology as well as vocabulary, writing systems and signed languages. Chapter previews and summaries, key words, a glossary and copious literature references help the reader understand and internalize what they have read, while activities at the end of each chapter reinforce key points'--
Includes bibliographical references and indexes.
Keywords: Typology (Linguistics).